Pengaruh Pemberian Aromaterapi Peppermint Terhadap Penurunan Kecemasan Pasien Pre Operasi Dengan Anestesi Spinal Pada Pasien Sectio Caesarea - Aidil Saputra , Andika; Tri Yudono , Danang; Bisma Yudha , Magenda; Susanto, Amin (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Preoperative anxiety is commonly experienced by patients before undergoing surgical procedures, including Caesarean section with spinal anesthesia. Peppermint aromatherapy is a non-pharmacological method that can be used to reduce anxiety. This study aimed to determine the effect of peppermint aromatherapy on reducing preoperative anxiety in the operating room at RST Padang. This research used a pre-experimental design with a one-group pretest posttest approach. The sample consisted of 36 patients selected using total sampling. Anxiety levels were measured before and after the administration of peppermint aromatherapy using an anxiety scale and analyzed using the Wilcoxon Signed Rank Test. The results showed that before the intervention, the majority of respondents experienced moderate anxiety (97.2%), while 2.8% had mild anxiety. After the intervention, 55.6% of respondents no longer experienced anxiety, and 44.4% were at a mild anxiety level. The Wilcoxon test showed a Z value of -5.263 with p < 0.001, indicating a significant difference in anxiety levels before and after the intervention. In conclusion, peppermint aromatherapy has been proven effective in reducing preoperative anxiety and can be considered as a complementary therapy in the management of patient anxiety before surgery. It is recommended that healthcare workers use this approach to enhance patient comfort during surgical preparation.